1992
DOI: 10.1111/j.1365-2958.1992.tb01501.x
|View full text |Cite
|
Sign up to set email alerts
|

DNA in dormant spores of Bacillus species is in an A‐like conformation

Abstract: SummaryThe DNA in dormant spores of Bacillus species is associated with a/|3-type smaii, acid-soiuble proteins (SASP), which are double-stranded DNA-binding proteins whose amino acid sequence has been highly conserved in evolution. In vitro these proteins bind most strongly to DNA which readily adopts an A-iike conformation, as binding of a/|3-type SASP causes DNA to assume an A-like conformation. As predicted by this conformational change in DNA, binding of a/ptype SASP to relaxed but covalently closed plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

1992
1992
2007
2007

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…Previous circular dichroism and Fourier transform infrared studies implied that binding of DNA to SspC, a characteristic member of the ␣/␤-type SASP family, promotes a conformational transition of DNA molecules from a B form to an A-like structure (19,31). It was proposed that this major conformational modification underlies the ability of ␣/␤-type SASP to protect spore DNA, by substantially modulating DNA photochemistry (19,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous circular dichroism and Fourier transform infrared studies implied that binding of DNA to SspC, a characteristic member of the ␣/␤-type SASP family, promotes a conformational transition of DNA molecules from a B form to an A-like structure (19,31). It was proposed that this major conformational modification underlies the ability of ␣/␤-type SASP to protect spore DNA, by substantially modulating DNA photochemistry (19,31).…”
Section: Discussionmentioning
confidence: 99%
“…It was proposed that this major conformational modification underlies the ability of ␣/␤-type SASP to protect spore DNA, by substantially modulating DNA photochemistry (19,31). It was also suggested that the change in DNA supercoiling detected following the interaction with SspC in vitro (20), as well as by DNA in spores (21), derives from the large alteration in the number of base pairs per helical turn that accompanies B-to-A DNA transition (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spore DNA is saturated with a group of unique proteins called ␣/␤-type SASP (184,186,(189)(190)(191). These proteins are synthesized only during sporulation in the developing spore and are degraded beginning early in spore germination.…”
Section: Parameters Contributing To Spore Resistancementioning
confidence: 99%
“…In this study, circular dichroism, mass spectrometry, ion mobility, and molecular dynamics calculations were performed on poly d(CG) n duplexes and mixed sequence duplexes from 18 to 30 bp long. For simplicity, the strands were named by their sequence and length so CG18 ϭ d(CG) 9 , CG22 ϭ d(CG) 11 , CG26 ϭ d(CG) 13 , CG30 ϭ d(CG) 15 , Mix18 ϭ dCAGTGAT(CG) 2 …”
mentioning
confidence: 99%